S117 Effects of Hypoxia on Eosinophil Apoptosis, Efferocytosis and Sensitivity to Glucocorticosteroids. (19th November 2012) - Porter, L; Cowburn, AS; Farahi, N; Fiddler, CA; Condliffe, AM; Chilvers, ER
Abstract : Many tissues including the skin, intestinal epithelium and potentially the airway operate at 'physiological' levels of tissue hypoxia with normal P O2 values below 3KPa. Both sterile and non-sterile inflammation exacerbates the degree of tissue hypoxia and predicates the need for granulocytes including eosinophils to operate efficiently under hypoxia. In these experiments we have examined the effects of hypoxia on eosinophil longevity and show that a P O2 below 3KPa severely attenuates the pro-apoptotic effect of dexamethasone. Human blood eosinophils were prepared from healthy donors using hetastarch-sedimentation and EasySep ® -immunomagenetic beads, and cultured in RPMI + 10% autologous serum for 6–24 h. Apoptosis and efferocytosis were quantified using standard morphology, AnV/PI staining and myeloperoxidase counter-stain methods. Hypoxic incubation (H) (media P O2 2.9±0.1 KPa) caused a marked survival response in eosinophils compared to normoxia (N) (% apoptosis at 24 h: N 16.3±3.0%; H 1.2±0.2%, n=5), which was of similar magnitude to that observed with IL-5 (N 4.2±0.3%). This hypoxic survival effect was mimicked by the iron chelator/2-oxyglutarate analogue DFO (10 mM) and DMOG (1 mM) and blocked in a concentration-dependent manner by the protein synthesis inhibitor cycloheximide. In preliminary experiments hypoxia also independently reduced the capacity of monocyte-derived macrophages to phagocytose apoptotic eosinophils as seen previously with neutrophils. Most strikingly, hypoxic incubation also reduced the normal pro-apoptotic effect of dexamethasone (1 µM) (% apoptosis at 24 h: N + Dex 27.6±3.9%, H + Dex 11.2±2.9%). qPCR analysis of the glucocorticosteroid-dependent gene GILZ and the hypoxia-HIF-1α-dependent gene GLUT1 demonstrated that the above suppression of dex-induced eosinophil apoptosis was not a consequence of the inhibition of steroid-induced transcriptional activity (mRNA fold change at 16 h: GILZ N 12.89±3.6, GILZ H 23.9±9.2; GLUT1 H (control) 28.5±7.2, GLUT1 H (Dex) 45.5±13.5, n=3). These data suggest that hypoxia can cause a profound effect on eosinophil longevity and macrophage uptake, and render these cells partially resistant to the pro-apoptotic effects of dexamethasone. This may impede the effective resolution of eosinophilic inflammation in vivo.